Functional genetic variation in pe/ppe genes contributes to diversity in Mycobacterium tuberculosis lineages and potential interactions with the human host - Gómez-González, Paula Josefina; Grabowska, Anna D.; Tientcheu, Leopold D.; Tsolaki, Anthony G.; Hibberd, Martin L.; Campino, Susana; Phelan, Jody E.; Clark, Taane G. (Frontiers in Microbiology, 2023)
Around 10% of the coding potential of Mycobacterium tuberculosis is constituted by two poorly understood gene families, the pe and ppe loci, thought be involved in host-pathogen interactions. Their repetitive nature and high GC content have hindered sequence analysis, leading to exclusion from whole-genome studies. To investigate the genetic diversity of the 169 pe/ppe genes, we performed a sequence analysis across 73 long-read assemblies representing seven different lineages of M. tuberculosis. The pe/ppe genes were classified into three groups based on the level of protein sequence conservation, finding that >50% were conserved, with indels in pe_pgrs and ppe_mptr sub-families being major drivers of structural variation. Gene rearrangements were observed between pe and pe_pgrs genes.Inter-lineage diversity revealed lineage-specific SNPs and indels, suggesting they are phylogenetically informative. Overall, improving our knowledge of these complex gene families may have insights into pathogenicity and inform the development of much-needed tools for tuberculosis control.